2017
DOI: 10.1371/journal.pone.0185361
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in the risk factors for in-hospital mortality and outcomes of ischemic stroke patients in rural areas of Taiwan

Abstract: Background and purposeSex-related differences in the clinical presentation and outcomes of stroke patients are issues that have attracted increased interest from the scientific community. The present study aimed to investigate sex-related differences in the risk factors for in-hospital mortality and outcome in ischemic stroke patients.MethodsA total of 4278 acute ischemic stroke patients admitted to a stroke unit between January 1, 2007 and December 31, 2014 were included in the study. We considered demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…Case fatality after 27 days and after 90 days was the same in men and women, after adjustment for the aforementioned covariates. Women’s all-cause mortality has been put forward to be lower after adjustments for relevant risk factors in some reports 7 , 13 but also, conversely, to be higher 24 , 30 or similar between men and women, 8 , 31 , 32 as in the present report. Variations in mortality between sexes may be caused by a disparity in the studied populations or may reflect differences in performed statistical adjustments.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Case fatality after 27 days and after 90 days was the same in men and women, after adjustment for the aforementioned covariates. Women’s all-cause mortality has been put forward to be lower after adjustments for relevant risk factors in some reports 7 , 13 but also, conversely, to be higher 24 , 30 or similar between men and women, 8 , 31 , 32 as in the present report. Variations in mortality between sexes may be caused by a disparity in the studied populations or may reflect differences in performed statistical adjustments.…”
Section: Discussionsupporting
confidence: 64%
“…6,9,13,28 This latter finding was not corroborated in the present study, which may partly explain the same stroke severity between men and women. Previous studies 28,30,31 have shown that cases of cardioembolic stroke are often more severe than those related to other causes.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the results of our study, in literature it was proven that the prevalence of stroke in females is lower than males, and several studies have shown that females suffered from more severe strokes, had higher short-term mortality than males, but long-term sex differences in mortality persist up to 5 years after stroke (10,11,12). Ghosh et al also reported that female patients had significantly higher incidence of poor outcome, but female gender was not a significant predictor of stroke severity and mortality (6).…”
Section: -4: Resultssupporting
confidence: 92%
“…Sex differences in the risk factor distribution, severity, and outcomes of ischemic stroke are multifactorial and related to genetics, environmental factors, and social influences [21][22][23]. Previous studies have revealed that older women with higher stroke severity at stroke onset have higher platelet counts, higher prevalence of cardioembolism, and more unfavorable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%